Bringing home Malaysians held in Syria could be tough - T.N., Alagesh (The New Straits Times Press (M) Bhd., 2020)
PEKAN: Malaysians stranded in Syria over suspected involvement in terrorism are discouraged from returning home by the Islamic State (IS), which continues to deceive them that the conflict is not over and the group will regain its lost territories soon.